An Ethnographic Account of the British Equestrian Virtue of Bravery, and Its Implications for Equine Welfare - Rosalie Jones McVey (Animals, 2021)
This article describes the virtue of bravery in British equestrian culture and suggests that riders’ tactics for bolstering bravery may have negative implications on equine welfare. These observations are based on 14 months of ethnographic research among amateur riders and the professionals who support them (n = 35), utilising participant observation and Dictaphone recordings. Riders suffering from ‘confidence issues’ could be belittled and excluded. Instructors’ approaches towards bolstering bravery involved encouraging riders to ‘get tough’—on both themselves and on their horses. Narrative theory is employed in this article to show that riders could demonstrate their own bravery through describing the horse as defiant. Alternate narrative possibilities existed, including describing the horse as needy patient and the rider as care provider. Riders were critically aware that veterinary diagnoses could be sought or avoided in line with riders’ own dispositions. ‘Diagnoses-seeking’ behaviours could be judged negatively by others and seen as evidence of unresolved fearfulness. In conclusion, the British equestrian cultural orientation towards bravery can be associated with stressful or painful training techniques, delayed or missed diagnoses of physiological pathologies, and poor training outcomes. Programs that aim to help riders to develop confidence without instilling a sense of ‘battle’ with the horse, and without ridiculing the rider, are likely to have positive implications on equine welfare and human safety.